1999
DOI: 10.1266/ggs.74.105
|View full text |Cite
|
Sign up to set email alerts
|

Structure and transcriptional control of the flagellar master operon of Salmonella typhimurium.

Abstract: The flhD and flhC genes constitute the flagellar master operon whose products are required for expression of all the remaining flagellar operons in Salmonella typhimurium. Here we report the molecular structure and in vivo and in vitro expression of the flhD operon. Nucleotide sequence analysis revealed that the upstream region of this operon contains the consensus sequence for the cAMP-CRP binding site. Primer extension analysis demonstrated six possible transcription start sites for this operon. They include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 35 publications
2
80
0
Order By: Relevance
“…These include the autogenous and global control by H-NS on flhDC master operon expression (Kutsukake, 1997) and the initiation of flhDC transcription (Soutourina et al, 1999 ;Yanagihara et al, 1999). On the other hand, some specificities may also exist in the response of these bacteria to acidic pH (Lin et al, 1995), including the PhoPQ-mediated acid tolerance response (ATR) (Bearson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These include the autogenous and global control by H-NS on flhDC master operon expression (Kutsukake, 1997) and the initiation of flhDC transcription (Soutourina et al, 1999 ;Yanagihara et al, 1999). On the other hand, some specificities may also exist in the response of these bacteria to acidic pH (Lin et al, 1995), including the PhoPQ-mediated acid tolerance response (ATR) (Bearson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The class 1 promoter is also known to require a number of other genes outside of the flagellar regulon for its expression (11,104,(114)(115)(116). Six transcriptional start sites have been mapped in the class 1 promoter region of Salmonella enterica serovar Typhimurium (132). It has also been demonstrated that cell cycle and flagellation are interdependent and that the flhDC genes are involved in coupling these processes (96,103).…”
Section: Class 1 Master Operonmentioning
confidence: 99%
“…This suggested that enhancement of class 2 expression might be mediated via overexpression of the FlhD and FlhC proteins in the flgM mutant. However, our recent experiment indicated that transcription of the wild type flhD operon on the chromosome is not enhanced by the flgM mutation in the absence of the multicopy flhDC + genes (Yanagihara et al, 1999). Therefore, there is a possibility that another unidentified factor(s) may be involved in regulation of the class 2 operons.…”
mentioning
confidence: 95%
“…-RNA polymerase (Yanagihara et al, 1999;Ikebe et al, 1999a, b). Class 1 is under positive control of at least two global regulators, Crp and H-NS, and under negative control of its own products, FlhD and FlhC (Kutsukake, 1997).…”
mentioning
confidence: 99%